العادات الاجتماعية التعاونية المستحدثة في ريف اللاذقية (الأعراس في مقاصف – التعزية في خيم) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تتنوع العادات الاجتماعية الجديدة بين السطحية العَرَضية (كالموضة) وبين المستمرّة والمرافقة لتغيرات المجتمع, كالعادات الاجتماعية التعاونية المستحدثة في ريف اللاذقية, التي يتم فيها قيام الأعراس في مقاصف خارج القرى, وقيام التعزية في خيم خارج المساكن, قامت هاتان العادتان منذ عدة سنوات, وهي لا تزال تلقى القبول والاستحسان. يتضمن البحث توضيحاً لمفهوم هاتين العادتين الاجتماعيتين المستحدثتين, وعرضاً لعواملهما النفسية الاقتصادية والاجتماعية كما يبين وظائفهما الاجتماعية والاقتصادية والإرشادية والتجديدية والترويحية, وينتهي البحث إلى عرض مظاهرهما كما تتجلى أمام سكان القرية وغيرهم. فالبحث دراسة موجزة في تكون العادات الاجتماعية . New social habits vary between superficially accidental habits andcontinuous habits that accompany the society changes such as the new-fashioned cooperative social habits in Rural Latakia. There, weddings are held in buffets outside the villages and the condolences are held in tents outside houses. These two habits have risen for many years and they still get the acceptance and satisfaction. This research includes an explanation for the concept of these two new-fashioned cooperative social habits, and a presentation of their social, economic and psychological factors. In addition, it shows their recreational, innovative, guiding, economic and social functions. The research ends with presenting the aspects of these habits as they appear before the rural people and others.